Application Of the Buffer Stock Method in The Inventory Information System: (Study On One Wholesale Company in Bandung) - Nurrohman, Zaki; Apriantsani, Dheni; Hamdani, Mohammad; Tay, En; Sambani, Egi Badar (Informatics Management, Engineering and Information System Journal, 2024)
This study aims to examine the inventory system employed by a wholesaler located in Bandung and offer suggestions to enhance the efficiency and effectiveness of inventory management. The research methodology is a case study incorporating interviews and firsthand observation of the company's inventory system. The results suggest that the company still needs to practice any particular approach for overseeing its inventory, resulting in difficulties in calculating suitable inventory levels and a failure to use technology in inventory management. Hence, the author advises the wholesaler in Bandung to enhance the utilization of technology in managing their inventory and proposes adopting a buffer stock approach for inventory control.